Functionalized nano silicon dioxide modified epoxy structural adhesive as well as preparation method and application thereof

By modifying the surface of nanosilicon dioxide and working in concert with epoxy resin, functionalized nanosilicon dioxide modified epoxy structural adhesives were developed, which solved the problems of poor toughness and poor temperature resistance in CFRP-reinforced steel structures, and achieved curing and high-performance structural adhesives at room temperature, reducing construction costs and difficulty.

CN119614122APending Publication Date: 2025-03-14HUNAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411885138.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing structural adhesives show defects such as poor toughness, poor adhesion and poor temperature resistance in CFRP reinforced steel structures, resulting in damage to reinforced specimens. The high price of structural adhesives on the market, limiting their wide application.

Method used

By modifying the nanosilicon dioxide surface and working in concert with components such as epoxy resin, functionalized nanosilicon dioxide modified epoxy structural glue was developed. The structural adhesive is curable at room temperature and has excellent tensile strength, elongation at break and strain energy. When using a combined curing agent, the heat resistance and toughness of the structural adhesive are further improved to meet the needs of steel bridge reinforcement.

Benefits of technology

The structural adhesive is cured at room temperature, reducing construction difficulty and cost, eliminating the need for complex heating equipment, and improving construction efficiency. At the same time, the tensile strength, elongation of break and strain energy of structural adhesives have been significantly improved, meeting the high-performance needs of CFRP reinforced steel structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614122A_ABST
    Figure CN119614122A_ABST
Patent Text Reader

Abstract

The invention discloses a functionalized nano silicon dioxide modified epoxy structural adhesive as well as a preparation method and application thereof. The epoxy structural adhesive is prepared from the following components in parts by mass: 100 to 130 parts of epoxy resin, 30 to 40 parts of a curing agent, 0.3 to 1.8 parts of functionalized nano silicon dioxide, 1.5 to 4.5 parts of a coupling agent, 1.5 to 4.5 parts of an accelerant, 0.35 to 1.05 parts of a thixotropic agent and 0.25 to 0.75 part of a de-foaming agent. The functionalized nano silicon dioxide is obtained by mixing nano silicon dioxide and dendritic polyamidoamine amino-grafted groups and then grafting the nano silicon dioxide and the dendritic polyamidoamine amino-grafted groups. According to the epoxy structural adhesive disclosed by the invention, the surface of the nano silicon dioxide is modified, the modified nano silicon dioxide is combined with the raw materials in the components, and the types of the curing agents are adjusted, so that the epoxy structural adhesive can be cured at room temperature, high-temperature-resistant and high-toughness properties can be realized, and the epoxy structural adhesive is particularly suitable for a CFRP (Carbon Fiber Reinforced Plastics) reinforced steel structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a functionalized nano-silicon dioxide modified epoxy structural adhesive and a preparation method and application thereof, belonging to the technical field of polymer materials. Background Art

[0002] The use of carbon fiber reinforced composite materials (CFRP) to strengthen fatigue damaged steel structures is a new type of steel structure reinforcement technology with great development prospects. The interfacial bonding performance between CFRP and steel is one of the key issues of this technology. Some research has been conducted at home and abroad, but it is still in the initial exploration stage. Existing studies have shown that the performance of the adhesive has the most significant effect on the interfacial bonding performance of CFRP-steel. At present, relevant literature is based on commercial structural adhesives for research, but the formula of commercial structural adhesives is confidential and expensive. They generally have the disadvantages of poor toughness and weak adhesion to the substrate, which leads to the destruction of reinforced specimens. At the same time, the heat resistance of structural adhesives on the market is generally poor, and the application scenarios are not wide. Therefore, it is urgent to develop a special structural adhesive suitable for CFRP reinforced steel structures. Summary of the invention

[0003] In view of the defects existing in the prior art, the first object of the present invention is to provide a functional nano-silica modified epoxy structural adhesive. The structural adhesive modifies the surface of nano-silica and works synergistically with the raw materials in the components. When a single type of curing agent is used, it can be cured at room temperature and has excellent tensile strength, elongation at break, strain energy and other properties. When a combined curing agent is used, the heat resistance and toughness of the structural adhesive can be further improved to meet the needs of steel bridge reinforcement.

[0004] The second object of the present invention is to provide a method for preparing a functionalized nano-silica modified epoxy structural adhesive. The method prepares the epoxy adhesive into AB components, which is not only conducive to storage, but also enables the components to react rapidly according to a preset ratio, thereby ensuring the performance stability of the epoxy structural adhesive. The method has the advantages of simple process flow, easy availability of raw materials and low cost.

[0005] The third object of the present invention is to provide an application of a functionalized nano-silica modified epoxy structural adhesive, which is used as a binder in CFRP reinforced steel structures. By changing the type of its curing agent, when it is a polyamine 105 curing agent, the epoxy structural adhesive not only has excellent performance but can also be cured at room temperature, and is very suitable for CFRP reinforced steel structure technology. The room temperature curing feature greatly reduces the construction difficulty and cost, and does not require complex heating equipment for auxiliary curing, thereby improving construction efficiency, thereby providing strong support for the widespread application of CFRP reinforced steel structure technology; when the curing agent is a polyamine 105 curing agent and a polyetheramine D230 curing agent, the epoxy curing agent has excellent high temperature resistance and high toughness, meets the heat resistance and toughness requirements of bridge reinforcement, and has a wide range of practical application scenarios.

[0006] In order to achieve the above technical purpose, the present invention provides a functionalized nano-silica modified epoxy structural adhesive, which comprises the following components by mass: 100-130 parts of epoxy resin, 30-40 parts of curing agent, 0.3-1.8 parts of functionalized nano-silica, 1.5-4.5 parts of coupling agent, 1.5-4.5 parts of accelerator, 0.35-1.05 parts of thixotropic agent and 0.25-0.75 parts of defoaming agent; the functionalized nano-silica is obtained by mixing nano-silica with dendritic polyamide amine and then grafting.

[0007] The functionalized nano-silicon dioxide in the technical solution of the present invention is a product obtained by grafting nano-silicon dioxide with dendritic polyamide amine-linked amino groups, and its surface is amino-linked. There are a large number of amino groups in the dendritic polyamide amine-linked amino groups, and the amino groups carry positive charges. Some amino groups can electrostatically interact with the negative charges of nano-silicon dioxide, thereby realizing the amino modification of the surface of silica. The amino groups can react with epoxy resin curing, and the interaction between molecular chains is enhanced. When subjected to tensile external forces, the molecular chains are difficult to slide, thereby effectively improving the tensile strength and the interface bonding ability of the epoxy resin matrix. At the same time, more cross-linked structures limit the extension of the molecular chains, and the molecular chains need to overcome more restrictions brought by the cross-linked structures before breaking, so that the elongation at break is also improved to a certain extent; under the action of load, the nano-silicon dioxide particles debond and form plastic cavities in the matrix. The rigid particles will hinder the expansion of cracks, form more microcracks, and form local plastic shear bands, absorbing a large amount of energy, thereby synergistically improving the strength and toughness of the adhesive. The curing agent in the structural adhesive is also crucial in the curing process of the structural adhesive. The presence of the functionalized nano-silica in the present invention will affect the diffusion and reactivity of the curing agent. Due to its special surface functional groups and chemical structure, it can promote a more uniform and sufficient reaction between the curing agent and the epoxy resin. During the curing process, a more complete three-dimensional network structure can be formed, which improves the overall performance of the structural adhesive, including the improvement of strain energy. A more perfect network structure can better store and release energy when subjected to external force, thereby improving strain energy; the silane coupling agent and the promoter in the present invention also play a vital role in the epoxy structural adhesive system. The silane coupling agent can act as a bridge connecting the inorganic and organic phases, and can also improve the dispersibility of the functionalized nano-silicon dioxide in the epoxy resin matrix during the curing reaction, prevent the nano-silicon dioxide from agglomerating, strengthen the interfacial bonding force, and effectively transfer the stress, thereby improving the overall performance. The promoter can accelerate the curing reaction of the epoxy structural adhesive and reduce the reaction activation energy. The functionalized nano-silicon dioxide affects its diffusion in the system and the exposure of active sites. The two work together to make the curing reaction more efficient, improve the degree of cross-linking to form a denser network structure, and enhance the interaction between molecular chains to improve the tensile strength, elongation at break, strain energy and other properties.

[0008] In the formula of the present invention, the dosage of functionalized nano-silica and curing agent has a great influence on the performance of the entire epoxy structural adhesive. Specifically, when the dosage of functionalized nano-silica is too low, its performance improvement effect on the epoxy structural adhesive is limited; when its dosage is too high, the nanomaterial is difficult to be effectively dispersed in the resin and even the performance of the structural adhesive is reduced. It is further preferred that the dosage of functionalized nano-silica is 0.75 to 1.2 parts, and it is further preferred that the dosage of functionalized nano-silica is 0.9 to 1.2 parts; in addition, the dosage of curing agent also has an important influence. Specifically, when the dosage of curing agent is too low, it is difficult to form a three-dimensional molecular network chain structure with a high degree of cross-linking, resulting in a decrease in the mechanical properties of the adhesive; when its dosage is too high, it will cause a violent reaction with the epoxy resin and an explosion phenomenon. It is further preferred that the dosage of curing agent is 32 to 35 parts, and it is further preferred that the dosage of curing agent is 34 to 35 parts.

[0009] As a preferred solution, the dendritic polyamide amine with amino groups is PAMAM G3-NH2, and its molecular weight is 6000-8000; the dendritic polyamide amine selected in the present invention is a third-generation macromolecule, which contains a large number of branches, and each branch contains multiple amino groups, has more positive charges, and is also easier to form a three-dimensional network structure. More preferably, the molecular formula is C 302 H 608 N 122 O 60 .

[0010] As a preferred solution, the particle size of the nano silicon dioxide is 100-600 nm. If the particle size of the nano silicon dioxide of the present invention is too small, it is more difficult to disperse; if the particle size is too large, the effect of improving toughness is not good.

[0011] As a preferred solution, the mass ratio of the nano-silica to the dendritic polyamide-amine-linked amino groups is (7-8): (2-3). If the ratio of the nano-silica to the dendritic polyamide-amine-linked amino groups in the present invention is too large, the number of the dendritic polyamide-amine-linked amino groups grafted on the surface of the nano-silica is small, and the interfacial chemical bonding force between the nano-silica and the epoxy resin matrix is ​​weakened. If the ratio of the nano-silica to the dendritic polyamide-amine-linked amino groups is too small, the resin matrix around the silica will be greatly deformed.

[0012] As a preferred solution, the grafting conditions are: temperature of 90-100° C. and time of 3.5-4.5 hours. Within the grafting temperature and time range selected by the present invention, the charge bonding between the silicon dioxide and the dendritic polyamide amine can be fully achieved.

[0013] As a preferred solution, the curing agent is at least one of condensing amine 105 curing agent and polyetheramine D230 curing agent. The inventors found that different types of curing agents have a relatively large impact on the performance of structural adhesives. The condensing amine 105 curing agent used in the present invention has a benzene ring structure in the molecular chain, and the structural adhesive has a large rigidity after curing and a small ductile deformation capacity, while the polyetheramine D230 molecular chain contains an ether bond, and the effect of the ether bond is opposite to that of the benzene ring. It makes it easy for the chain segment to rotate internally around the two ends of the ether bond, which can increase the flexibility of the main chain, thereby improving the flexibility of the structural adhesive. When only the condensing amine 105 curing agent is further used, it interacts with functionalized nano-silica and other auxiliary ingredients, and not only has excellent mechanical properties but also can be cured at room temperature. When the polyamine 105 curing agent and the polyetheramine D230 curing agent are further used in combination, a structural adhesive with both heat resistance and toughness can be obtained, and as the amount of polyetheramine D230 increases, the tensile strength and elastic modulus of the structural adhesive at high temperature gradually decrease, and the elongation at break and strain energy first increase and then decrease. It is further preferred that the weight ratio of the polyamine 105 curing agent and the polyetheramine D230 curing agent is (1-2): (1-2). It is further preferred that the weight ratio of the polyamine 105 curing agent and the polyetheramine D230 curing agent is 1:2.

[0014] In the present invention, different types of curing agents can be used in combination according to different application scenarios, so as to achieve differences in the performance of the epoxy structural adhesive and be used in different scenarios.

[0015] As a preferred solution, the epoxy resin includes at least one of bisphenol A type E51 and E44; the coupling agent includes at least one of silane coupling agents KH-560 and KH570; the accelerator includes DMP-30; the thixotropic agent includes HB-139; and the defoaming agent includes D240.

[0016] The present invention also provides a method for preparing a functionalized nano-silica modified epoxy structural adhesive, which comprises mixing components including epoxy resin, functionalized nano-silica, a coupling agent and a thixotropic agent to obtain a component A, then mixing a curing agent, an accelerator and a defoaming agent to obtain a component B, and finally mixing the A and B components to obtain the adhesive.

[0017] The present invention adopts the form of AB two components, which is not only conducive to storage, but also enables each component to react quickly according to a preset ratio, thereby ensuring the performance stability of the epoxy structural adhesive, and has the advantages of simple process flow, easy availability of raw materials and low cost.

[0018] As a preferred solution, the mass ratio of component A to component B is 100:(25-35).

[0019] The present invention provides a method for preparing a functionalized nano-silicon dioxide modified epoxy structural adhesive, which specifically comprises the following steps:

[0020] 1) Heat the epoxy resin to 50-60°C to dissolve possible crystals in the resin and reduce the viscosity of the resin; then add the functionalized nano-SiO2 and heat it to 70-80°C, and stir it mechanically for 30-50 minutes to effectively disperse the nanoparticles in the epoxy resin; then cool the mixture to 40-50°C, add the coupling agent, and stir it mechanically for 10-15 minutes; finally, add the thixotropic agent, keep the mixture temperature unchanged, stir it mechanically for 10-15 minutes, and naturally cool it to room temperature to prepare component A.

[0021] 2) Weigh the curing agent, add the accelerator and the defoaming agent, and mechanically stir at 40-45° C. for 15-20 minutes to prepare component B.

[0022] 3) Mix components A and B, and mechanically stir them at room temperature for 10 to 15 minutes to obtain a functionalized nano-silica modified epoxy structural adhesive.

[0023] The present invention also provides an application of a functionalized nano-silicon dioxide modified epoxy structural adhesive, which is used as an adhesive in CFRP reinforced steel structures.

[0024] As a preferred solution, when the curing agent is condensation amine 105 curing agent, the curing conditions of the adhesive are: temperature of 20 to 90°C and time of 2 hours to 6 days. At this time, the epoxy structural adhesive of the present invention not only has excellent performance but can also be cured at room temperature, and is very suitable for CFRP reinforced steel structure technology. The room temperature curing property greatly reduces the construction difficulty and cost, does not require complex heating equipment to assist in curing, and improves the construction efficiency, thereby providing strong support for the wide application of CFRP reinforced steel structure technology.

[0025] As a preferred solution, when the curing agent is polyamine 105 curing agent and polyetheramine D230 curing agent, the curing conditions of the adhesive are: temperature of 90-110°C and time of 2-3 hours. When the two curing agents are combined, even if the curing is carried out for a long time at room temperature, the effect of using only polyamine 105 curing agent cannot be achieved.

[0026] Compared with the prior art, the technical solution of the present invention brings about the following innovative and beneficial technical effects:

[0027] 1) The functionalized nano-silica of the present invention is obtained by grafting nano-silica with dendritic polyamide amines. Its special structure enhances the interaction between molecular chains, and the molecular chains are difficult to slide when subjected to tensile external forces, effectively improving the tensile strength and the interfacial bonding ability of the epoxy resin matrix. More cross-linked structures improve the elongation at break. Under load, the nano-silica particles debond and form plastic holes in the matrix. The rigid particles will hinder the expansion of cracks, forming more microcracks, and will form local plastic shear bands, absorbing a large amount of energy, thereby synergistically improving the strength and toughness of the adhesive. The curing agent interacts with the functionalized nano-silica, prompting the curing agent to react more evenly and fully with the epoxy resin, forming a more complete three-dimensional network structure, and improving strain energy. The coupling agent acts as a bridge connecting the inorganic and organic phases, improves the dispersibility of the functionalized nano-silica in the epoxy resin matrix, and synergizes with the accelerator to improve the degree of crosslinking and the interaction of the molecular chains, further improving the overall performance of the structural adhesive. The epoxy structural adhesive of the present invention has excellent comprehensive properties including high tensile strength, high elongation at break, high strain energy, etc.

[0028] 2) The present invention makes the tensile strength, elongation at break and strain energy of epoxy structural adhesive 1.44-1.81 times, 1.03-7.80 times and 1.17-35.79 times of those of common commercial structural adhesives by reasonably matching functionalized nano-silicon dioxide with other raw materials. The peak shear stress, limit slip, interface stiffness and interface fracture energy of the overlapped specimens using the structural adhesive are 1.02-2.62 times, 1.05-1.61 times, 3.49-4.81 times and 1.52-5.58 times of those of the overlapped specimens using the common commercial structural adhesives. It can meet the actual application requirements; and the raw materials used are low in cost, the reagent dosage is small, the manufacturing process is simple, it meets the requirements of large-scale production, and has broad market prospects.

[0029] 3) The preparation process of the present invention is simple, the raw materials are easily available, and the cost of raw materials is low, which meets the requirements of large-scale production. It is further preferred that the curing agent is condensed amine 105 curing agent. In terms of application, the epoxy structural adhesive can be cured under warm conditions, which is particularly suitable for use in CFRP reinforced steel structures. This feature reduces the construction difficulty and cost, does not require complex heating equipment to assist in curing, improves construction efficiency, and far exceeds the existing technology in terms of adaptability to the structure and convenience of practical application; at the same time, it is further preferred that the curing agent is condensed amine 105 curing agent and polyetheramine D230 curing agent, which has excellent bearing capacity and interface fracture energy when applied to CFRP-steel plate tower connection specimens. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the structural flow of the functionalized nano-silica prepared in Example 1.

[0031] Figure 2The SEM images of the tensile cross-section of the CFRP-steel plate tower joint specimens prepared by the structural adhesives prepared in Comparative Example 1 and Examples 2 to 4 are shown in FIG. Figure 2 (a) is ZR10, Figure 2 (b) is ZR12, Figure 2 (c) is ZR13, Figure 2 (d) is ZR14, Figure 2 (e) is ZR15.

[0032] Figure 3 The tensile stress-strain curves of the structural adhesives prepared in Comparative Example 1 and Examples 1 to 5 applied to CFRP-steel plate tower joint specimens.

[0033] Figure 4 Shear stress-strain curves of the structural adhesives prepared in Comparative Example 1 and Examples 1 to 5 applied to CFRP-steel plate tower joint specimens.

[0034] Figure 5 For Example 2 ( Figure 5 (a)), Example 8 ( Figure 5 (b)) and Example 9 ( Figure 5 (c)) SEM image of the tensile cross-section of the prepared structural adhesive applied to the CFRP-steel plate tower connection specimen.

[0035] Figure 6 DMA dynamic thermodynamic analysis curves of the structural adhesives of Examples 2 and 6 to 9 at a curing temperature of 90°C.

[0036] Figure 7 The CFRP-steel double lap joint of the present invention is in the form of ( Figure 7 (a)) and strain gauge arrangement ( Figure 7 (b)).

[0037] Figure 8 This is a tensile test of the CFRP-steel double lap joint specimen of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be further described below in conjunction with specific embodiments of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; these embodiments are only for a better understanding of the present invention, rather than limiting the scope of protection of the present invention.

[0039] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0040] The particle size of the nano silicon dioxide used in the present invention is 100-600nm.

[0041] Example 1

[0042] This embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by mass: 120 parts of E51 epoxy resin, 35 parts of condensation amine 105 curing agent, 0.3 parts of functionalized nano-silica, 3 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0043] The implementation process is as follows:

[0044] Nano-silica and dendritic polyamidoamine with amino groups were mixed in a mass ratio of 7:3, added into a reactor at a temperature of 95°C, and mechanically stirred for 4 hours to prepare functionalized nano-silica. The structural schematic diagram is shown in Figure 1, wherein the dendritic polyamidoamine with amino groups is PAMAM G3-NH2 (purchased from Hangzhou Xinqiao Biotechnology Co., Ltd.), with a molecular weight of 6909 and a molecular formula of: C 302 H 608 N 122 O 60 .

[0045] The epoxy resin was heated to 60°C to dissolve possible crystals in the resin and reduce the viscosity of the resin; then functionalized nano-SiO2 was added. It was heated to 80°C and mechanically stirred at this temperature for 30 minutes to effectively disperse the nanoparticles in the epoxy resin; then the mixture was cooled to 50°C, a coupling agent was added, and mechanical stirring was performed for 15 minutes; finally, a thixotropic agent was added, and the mixture temperature was kept constant at 50°C, mechanical stirring was performed for 15 minutes, and the mixture naturally cooled to room temperature to prepare component A. The curing agent was weighed separately, and the accelerator and defoaming agent were added, and mechanical stirring was performed at 40°C for 15 minutes to prepare component B. Then, components A and B were mixed at a mass ratio of 100:35, and mechanical stirring was performed at room temperature for 10 minutes to obtain a functionalized nano-silica modified epoxy structural adhesive, named ZR11.

[0046] This embodiment uses a curing temperature of 25° C. and a curing time of 2 hours.

[0047] Example 2

[0048] This embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by mass: 120 parts of E51 epoxy resin, 35 parts of condensation amine 105 curing agent, 0.6 parts of functionalized nano-silica, 3 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0049] The implementation process of this embodiment is the same as that of embodiment 1, and the obtained structural adhesive is named ZR12 and also named GY31.

[0050] Example 3

[0051] The present embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by mass: 120 parts of E51 epoxy resin, 35 parts of condensation amine 105 curing agent, 0.9 parts of functionalized nano-silica, 3 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0052] The implementation process of this embodiment is the same as that of embodiment 1, and the obtained structural adhesive is named ZR13.

[0053] Example 4

[0054] This embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by mass: 120 parts of E51 epoxy resin, 35 parts of condensation amine 105 curing agent, 1.2 parts of functionalized nano-silica, 3 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0055] The implementation process of this embodiment is the same as that of embodiment 1, and the obtained structural adhesive is named ZR14.

[0056] Example 5

[0057] The present embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by weight: 110 parts of E44 epoxy resin, 32 parts of condensation amine 105 curing agent, 1.8 parts of functionalized nano-silica, 3 parts of KH-570 coupling agent, 2 parts of DMP-30 accelerator, 0.5 parts of HB-139 thixotropic agent, and 0.3 parts of D240 defoaming agent.

[0058] The implementation process of this embodiment is the same as that of embodiment 1, and the obtained structural adhesive is named ZR15.

[0059] Example 6

[0060] The present embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by mass: 120 parts of E51 epoxy resin, 23.33 parts of condensation amine 105 curing agent, 11.67 parts of polyether amine D230 curing agent, 0.6 parts of functionalized nano-silica, 2 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0061] The implementation process of this embodiment is the same as that of embodiment 1, but the curing temperature is 90° C., the curing time is 2 h, and the obtained structural adhesive is named GY32.

[0062] Example 7

[0063] The present embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by mass: 120 parts of E51 epoxy resin, 17.5 parts of condensation amine 105 curing agent, 17.5 parts of polyether amine D230 curing agent, 0.6 parts of functionalized nano-silica, 2 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0064] The implementation process of this embodiment is the same as that of embodiment 1, but the curing temperature is 90° C., the curing time is 2 h, and the obtained structural adhesive is named GY33.

[0065] Example 8

[0066] The present embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by mass: 120 parts of E51 epoxy resin, 11.67 parts of condensation amine 105 curing agent, 23.33 parts of polyether amine D230 curing agent, 0.6 parts of functionalized nano-silica, 2 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0067] The implementation process of this embodiment is the same as that of embodiment 1, but the curing temperature is 90° C. and the curing time is 2 h. The obtained structural adhesive is named GY34.

[0068] Example 9

[0069] This embodiment is a functionalized nano-silica modified epoxy structural adhesive, which is made of the following raw materials in parts by weight: 120 parts of E51 epoxy resin, 35 parts of polyetheramine D230 curing agent, 0.6 parts of functionalized nano-silica, 2 parts of KH-560 coupling agent, 3 parts of DMP-30 accelerator, 0.7 parts of HB-139 thixotropic agent, and 0.5 parts of D240 defoaming agent.

[0070] The implementation process of this embodiment is the same as that of embodiment 1, but the curing temperature is 90° C., the curing time is 2 h, and the obtained structural adhesive is named GY35.

[0071] Example 10

[0072] The formula of the structural adhesive in this embodiment is the same as that in embodiment 8, except that the curing temperature is 25° C. and the curing time is 7 days.

[0073] Embodiment 11

[0074] The formula of the structural adhesive in this embodiment is the same as that in embodiment 8, except that the curing temperature is 110° C. and the curing time is 2 h.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 3 is that no functionalized nano-silica is added, and the other steps and conditions are the same. The obtained structural adhesive is named ZR10.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 3 is that an equal mass portion of non-functionalized nano-silicon dioxide is added, and the other conditions and steps are the same.

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 3 is that the mass ratio of nano-silica and dendritic polyamidoamine-linked amino group PAMAM G3-NH2 is changed to 9:1, and the other conditions and steps are the same.

[0081] Comparative Example 4

[0082] The difference between this comparative example and Example 3 is that the amount of condensation amine 105 curing agent is changed to 25 parts, and the other conditions and steps are the same.

[0083] Examples 1 to 9, Comparative Examples 1 to 4 and commercially available structural adhesives were subjected to performance tests. The results are shown in Table 1. The specific test methods for tensile strength, elongation at break, elastic modulus and strain energy were carried out in accordance with the national standard GB / T2567-2008 "Test methods for properties of resin castings".

[0084] Table 1 Performance test results of Examples 1 to 9 and Comparative Examples 1 to 4 and commercially available structural adhesives

[0085]

[0086]

[0087] Examples 1 to 11 and Comparative Examples 1 to 4 and commercially available structural adhesives were used in the CFRP reinforcement steel structure technology. The adhesive CFRP-steel plate double lap joint test pieces were designed and manufactured with reference to the American ASTM D3528-96 (2008) standard. Figure 7 (a) and Figure 7 (b) The tensile shear test of the CFRP plate-steel plate lap specimen was carried out on a 300kN quasi-static tensile testing machine equipped with a high and low temperature chamber. The loading was carried out using displacement control at a rate of 0.3mm / min. The loading device is shown in Figure 8 The performance test of the samples was carried out, and the test results are shown in Table 2.

[0088] Table 2 Mechanical properties of CFRP-steel double lap interface

[0089]

[0090]

[0091] In Table 2, ZR** and GY** represent the names of structural adhesives, CT** represents the curing temperature of the structural adhesive, and ST** represents the working temperature of the CFRP-steel plate lap joint specimen.

[0092] The CFRP-steel plate interface bonding-slip constitutive parameters of Example 4 and commercially available structural adhesives were obtained, and the results are shown in Table 3.

[0093] Table 3 Results of CFRP-steel interface bonding-slip constitutive parameters of Example 4, Comparative Examples 1-2 and commercially available structural adhesives

[0094]

[0095]

[0096] Comparison of the glass transition temperatures of Example 8, Example 10 and Example 11. The results are shown in Table 4.

[0097] Table 4

[0098] serial number Tangent method / ℃ Loss modulus method / ℃ Loss factor method / ℃ Experimental Example 8 71.0 72.6 85.8 Experimental Example 10 68.1 70.7 79.5 Experimental Example 11 70.4 75.3 89.8

[0099] The effects of different working temperatures on the mechanical properties of the structural adhesive during the application of the structural adhesive in Example 8 were investigated. The results are shown in Table 5.

[0100] Table 5 Test results of the influence of different working temperatures on mechanical properties in Example 8

[0101]

[0102] The influence of different working temperatures on the mechanical properties of the CFRP steel double lap joint during the application of the structural adhesive in Example 8 was investigated. The results are shown in Table 6.

[0103] Table 6 Comparison of tensile tests of CFRP-steel double tower joints under different test environments in Example 8

[0104]

[0105]

[0106] Note: Take GY34-2.0-90-25-1 as an example to explain the meaning of each data: GY34 represents the name of the structural adhesive, 2.0 represents the curing time of 2h, 90 represents the curing temperature of 90℃, 25 represents the test environment temperature of 25℃, and 1 represents the first experiment of the parallel experiment. Failure mode: a represents the interface failure between CFRP and adhesive layer; b represents the interface failure between steel and adhesive layer; d represents the delamination failure of CFRP plate.

[0107] Figure 2 The SEM scans of the tensile section of the adhesive are shown in Figure 10. The scanned photo shows that the amount of nano-SiO2 added is 0wt.%. The fracture surface is very smooth and the crack direction is single, indicating that the section is brittle failure. From the scanned photos of ZR12 to ZR14, it can be seen that with the increase of the amount of nano-SiO2 added, the small holes left by the peeling and pulling out of the nano-SiO2 on the tensile section become more and more dense, and the roughness of the tensile section increases significantly, with more obvious plastic deformation. In addition, the nano-SiO2 is evenly distributed in the adhesive, and there is no agglomeration of nano-particles. It has good compatibility with the epoxy resin matrix. Under the action of load, the adhesive with nano-SiO2 particles produces stress concentration at the nano-SiO2, and the adhesive around the particles undergoes yield deformation, resulting in a local plastic shear band that absorbs a lot of energy, thereby achieving a toughening effect. At the same time, the cracks on the substrate continue to grow under the action of load and will encounter nearby rigid particles, causing the cracks to be distorted and forming secondary cracks, which in turn hinder and passivate the crack propagation. At this time, if you want to form a new crack front, you need to absorb more energy, that is, the outside world needs a greater force to completely split the substrate. In addition, SiO2 nanoparticles can debond in the triaxial stress field in front of the crack tip, thereby forming dense plastic voids in the epoxy adhesive, which greatly improves the toughness of the adhesive.

[0108] Depend on Figure 3 It can be seen that with the increase of the mass fraction of functionalized nano-silica, the tensile stress-strain curve of the structural adhesive changes significantly. When the mass fraction is 0, the stress-strain relationship is basically a straight line from the beginning of loading to the entire process of fracture, indicating that the structural adhesive is very brittle; when the mass fraction is 0.3 to 1.2, while maintaining a large tensile strength, the ductility is greatly improved, and the stress-strain curve changes from linear to nonlinear, with good toughness.

[0109] Depend on Figure 3 As shown in Table 1, the tensile strength, elongation at break, and strain energy of the functionalized nano-silica modified epoxy structural adhesive of the present invention are greater than those of commonly used commercial structural adhesives, and the elastic modulus is less than that of commonly used commercial structural adhesives. The tensile strength is 1.44 to 1.81 times that of commonly used commercial structural adhesives, the elongation at break is 1.03 to 7.80 times that of commonly used commercial structural adhesives, and the strain energy is 1.17 to 35.79 times that of commonly used commercial structural adhesives. Moreover, when no functionalized nano-silica is added or non-functionalized nano-silica is added or the mass ratio of silica to dendritic polyamide amine-bonded amino groups is not within the range during the modification process or the amount of curing agent used is small, the tensile strength, elongation at break, and shear strength of the resulting structural adhesive will all drop significantly.

[0110] As can be seen from Table 3, the peak shear stress, limit slip, interface stiffness and interface toughness of the overlapped specimens of the structural adhesive of Example 4 of the present invention are greater than those of the overlapped specimens of the commonly used commercial structural adhesives. Among them, the peak shear stress is 1.02 to 2.62 times that of the commonly used commercial structural adhesives, the limit slip is 1.05 to 1.61 times that of the commonly used commercial structural adhesives, the interface stiffness is 3.49 to 4.81 times that of the commonly used commercial structural adhesives, and the interface toughness is 1.52 to 5.58 times that of the commonly used commercial structural adhesives. Under the same conditions of bonding width, CFRP plate geometric parameters and mechanical parameters, the ultimate bearing capacity, interface slip stiffness and fracture energy of the CFRP-steel interface using the modified nano-silica epoxy structural adhesive of the present invention are greatly improved.

[0111] As shown in Table 4, the glass transition temperatures obtained by the tangent method, loss modulus method and loss factor method in Examples 8, 10 and 11 all increase with the increase of curing temperature, and there is a relationship of tangent method < loss modulus method < loss factor method. The glass transition temperatures of the adhesives in Examples 8 and 11 are slightly different, while the glass transition temperature of Example 10 is slightly lower and the curing time is relatively longer. Therefore, considering various factors comprehensively, it can be concluded that when the curing agent is a combination of polyamine 105 curing agent and polyetheramine D230 curing agent, the preferred curing conditions are the curing conditions of Example 8.

[0112] As shown in Table 5, the mechanical properties of the structural adhesive of Example 8 change significantly at different working temperatures. With the increase of temperature, the tensile strength and elastic modulus of the structural adhesive of Example 8 gradually decrease. The tensile strength and elastic modulus at 55°C are reduced by 71.43% and 42.47% respectively compared with those at 25°C. In addition, with the increase of temperature, the elongation at break and the strain energy of Example 8 increase first and then decrease. The elongation at break and the strain energy at 55°C are increased by 601.64% and 144.38% respectively compared with those at 25°C, and the elongation at break and the strain energy at 90°C are reduced by 35.58% and 94.55% respectively compared with those at 55°C.

[0113] Depend on Figure 5 It can be seen that the tensile section of Example 2 is relatively smooth, the crack direction is single, and it is in a through-state; the tensile section of the adhesive of Example 9 has more obvious plastic deformation than that of Example 2; the tensile section of the adhesive of Example 8 has more short microcracks, and the section roughness is significantly increased, showing better toughness.

[0114] Depend on Figure 6(a) It can be seen that when only polyamine 105 curing agent is used or polyamine 105 is mixed with polyetheramine D230, the storage modulus of the structural adhesive is slightly different; when only polyetheramine D230 curing agent is used, the storage modulus of the structural adhesive is significantly reduced. The glass transition temperatures Tg,S based on the storage modulus of the structural adhesives of Example 2 and Example 9 (i.e., the temperature corresponding to the intersection of the corner tangents on the storage modulus curve) are 92.9°C and 56.3°C, respectively. The Tg,S of Example 8 is between the two, which is 71.0°C. Figure 6 (b) It can be seen that with the increase of the proportion of polyetheramine D230 in the mixed curing agent, the loss modulus peak of the structural adhesive first increases and then decreases, and Example 8 has the largest loss modulus peak; the glass transition temperature Tg,L based on the loss modulus (i.e., the temperature corresponding to the peak of the loss modulus curve) gradually decreases with the increase of the proportion of polyetheramine D230. The Tg,L of Example 2 is 94.9°C, the Tg,L of Example 9 is only 56.3°C, and the Tg,L of Example 8 is between the two, which is 72.6°C. Figure 6 (c) It can be seen that with the increase of the proportion of polyetheramine D230 in the mixed curing agent, the loss factor peak of the structural adhesive first decreases and then increases (the larger the loss factor, the greater the viscosity of the material; the smaller the loss factor, the greater the elasticity of the material); the glass transition temperatures Tg,T (i.e., the temperature corresponding to the peak of the loss factor curve) of the structural adhesives of Examples 2 and 9 based on the loss factor are 105.3°C and 68.7°C, respectively, and the Tg,L of Example 8 is between the two, which is 85.8°C.

[0115] In summary, the functionalized nano-silica modified structural adhesive developed by the present invention is a synergistic effect of the components, dosages and amino modification, so the overall performance is better than that of commonly used commercial structural adhesives, and the material price is more economical, more suitable for CFRP reinforcement steel structure projects, and has significant progress and practical value.

[0116] The above embodiments are only for better explanation of the principles and practical applications of the present invention, so that those skilled in the relevant technical field can better understand and utilize the present invention, but they are not intended to limit the patent scope of the present invention. All equivalent changes made using the contents of the present invention are within the patent protection scope of the present invention.

Claims

1. A functionalized nano-silica modified epoxy structural adhesive, characterized in that: The invention comprises the following components by weight: 100-130 parts of epoxy resin, 30-40 parts of curing agent, 0.3-1.8 parts of functionalized nano-silicon dioxide, 1.5-4.5 parts of coupling agent, 1.5-4.5 parts of accelerator, 0.35-1.05 parts of thixotropic agent and 0.25-0.75 parts of defoaming agent; the functionalized nano-silicon dioxide is obtained by mixing nano-silicon dioxide and dendritic polyamide amine and then grafting them.

2. The functionalized nano-silica modified epoxy structural adhesive according to claim 1, characterized in that: The dendritic polyamidoamine amino group is PAMAM G3-NH2, and its molecular weight is 6000-8000.

3. A functionalized nano-silica modified epoxy structural adhesive according to claim 2, characterized in that: The particle size of the nano silicon dioxide is 100 to 600 nm; The mass ratio of the nano-silicon dioxide to the dendritic polyamide amine-bonded amino group is (7-8): (2-3).

4. The functionalized nano-silica modified epoxy structural adhesive according to claim 2, characterized in that: The grafting conditions are: temperature of 90-100° C. and time of 3.5-4.5 h.

5. A functionalized nano-silica modified epoxy structural adhesive according to any one of claims 1 to 4, characterized in that: The curing agent is at least one of polyamine 105 curing agent and polyetheramine D230 curing agent.

6. The functionalized nano-silica modified epoxy structural adhesive according to claim 5, characterized in that: The epoxy resin includes at least one of bisphenol A type E51 and E44; The coupling agent includes at least one of silane coupling agents KH-560 and KH570; The accelerator includes DMP-30; The thixotropic agent includes HB-139; The defoaming agent includes D240.

7. The method for preparing a functionalized nano-silica modified epoxy structural adhesive according to any one of claims 1 to 6, characterized in that: Components including epoxy resin, functionalized nano-silica, coupling agent and thixotropic agent are mixed to obtain component A, and then a curing agent, an accelerator and a defoaming agent are mixed to obtain component B. Finally, components A and B are mixed to obtain the product.

8. The method for preparing a functionalized nano-silica modified epoxy structural adhesive according to claim 7, characterized in that: The mass ratio of the component A to the component B is 100:(25-35).

9. The use of a functionalized nano-silicon dioxide modified epoxy structural adhesive according to any one of claims 1 to 6, characterized in that: Used as an adhesive in CFRP reinforced steel structures.